Climate change and the northern Russian treeline zone - MacDonald, G.M (The Royal Society, 2007)
The Russian treeline is a dynamic ecotone typified by steep gradients in summer temperature and regionally variable gradients in albedo and heat flux. The location of the treeline is largely controlled by summer temperatures and growing season length. Temperatures have responded strongly to twentieth-century global warming and will display a magnified response to future warming. Dendroecological studies indicate enhanced conifer recruitment during the twentieth century. However, conifers have not yet recolonized many areas where trees were present during the Medieval Warm period (ca AD 800–1300) or the Holocene Thermal Maximum (HTM; ca 10 000–3000 years ago). Reconstruction of tree distributions during the HTM suggests that the future position of the treeline due to global warming may approximate its former Holocene maximum position. An increased dominance of evergreen tree species in the northern Siberian forests may be an important difference between past and future conditions. Based on the slow rates of treeline expansion observed during the twentieth century, the presence of steep climatic gradients associated with the current Arctic coastline and the prevalence of organic soils, it is possible that rates of treeline expansion will be regionally variable and transient forest communities with species abundances different from today's may develop.